Main flaws of the collateralized debt obligation's valuation before and during the 2008/2009 global turmoil - Petra Benešová; Petr Teplý (Charles University in Prague, Institute of Economic Studies (IES), 2010)
As a result of the 2008 financial crisis, the world credit markets stalled significantly and raised the doubts of market participants and policymakers about the proper and fair valuation of financial derivatives and structured products such as collateralized debt obligations (CDOs). The aim of the paper is to contribute to the understanding of CDOs and shed light on CDO valuation based on data before and during the current financial upheaval. We present the One Factor Model based on a Gaussian Copula and test five hypothesizes. Based on the results we discovered four main deficiencies of the CDO market. For our modelling we used data of the CDX NA IG 5Y V3 index from 20 September 2007 until 27 February 2009 and its quotes we appropriately transform into CDO quotes. Based on the results we discovered four main deficiencies of the CDO market: i) an insufficient analysis of underlying assets by both investors and rating agencies; ii) the valuation model was usually based only on expected cash-flows when neglecting other factors such mark-to-market losses or correlation risk; iii) mispriced correlation; and finally iv) the mark-to-market valuation obligation for financial institutions should be reviewed. Based on the mentioned recommendations we conclude that the CDO market has a chance to be regenerated. However, the future CDO market would then be more conscious, driven by smarter motives rather than by poor understanding of risks involved in CDOs.
Keywords: G01; G32; C63; 330; collateralized debt obligations; Gaussian Copula; valuation; securitization; Asset-Backed Securities; Verbriefung; Finanzanalyse; Finanzkrise; Kopula (Mathematik)